Scooby-Doo! World of Mystery 37 England - Stonehenge - Creative Plus Publishing Ltd (De Agostini Uk Ltd, 2005)
The gang visit Stonehenge in England where Shaggy and Scooby turn into druids and go to a rock concert!
Keywords: Juvenile literature-Fiction